Differentiation-inducing activity of lupane triterpenes on a mouse melanoma cell line - Hata, Keishi (Kluwer Academic Publishers, 2007)
Lupane triterpenes were found to promote melanogenesis, a hallmark of B16 2F2 mouse melanoma cell differentiation. Studies of the structure-activity relationships demonstrated that the keto function at C-3 of the lupane skeleton played important roles in the melanogenic activities of lupane triterpenes on melanoma cells. The carbonyl group at C-17 of lupane triterpenes was essential against their apoptosis-inducing activity against human cancer cells via the inhibition of topoisomerase I. We investigated whether signaling mechanisms were involved in the stimulative effects of lupane triterpenes on the melanogenesis of B16 2F2 cells. In experiments using selective inhibitors against various signal transduction molecules and Western blotting analysis, it was suggested that p38 MAPK was involved in melanoma cell differentiation as a downstream effector of PKA. Lupeol (compound 1), a lupane triterpene, induced dendrite formations, a morphological hallmark of B16 2F2 cell differentiation by rearrangement of the actin cytoskeleton. The activation of cofilin, an actin depolymerizing factor, by compound 1 caused actin fiber disassembly in B16 2F2 cells. Furthermore, compound 1 was shown to inhibit the cell motilities of human melanoma and neuroblastoma in vitro.